Highly selective macrocyclic ring-closing metathesis of terminal olefins in non-chlorinated solvents at low dilution. Issue 2 (20th December 2018) - Dumas, Adrien; Colombel-Rouen, Sophie; Curbet, Idriss; Forcher, Gwénael; Tripoteau, Fabien; Caijo, Frédéric; Queval, Pierre; Rouen, Mathieu; Baslé, Olivier; Mauduit, Marc
Abstract : New ruthenium complexes featuring two unsymmetrical NHCs proved to be highly selective in macrocyclic RCM performed in green solvents at low dilution. Abstract : A set of new ruthenium–indenylidene complexes bearing two unsymmetrical unsaturated N -cycloalkyl-NHC ligands were synthesized. These catalysts proved to be highly selective in the macrocyclic ring-closing metathesis performed in non-chlorinated solvents at low dilution (0.01 M). Without the requirement of benzoquinone derivatives to prevent the isomerisation side reactions, this environmentally friendly catalytic process promoted the synthesis of macrocyclic odorant molecules with remarkable >99% purity.